Early prescription of biological agents for immune-mediated inflammatory diseases: opportunities and prospects. An expert’s opinion - D. I. Abdulganieva; A. L. Bakulev; E. A. Belousova; A. V. Veselov; T. V. Korotaeva; A. M. Lila; E. Yu. Loginova; E. V. Sokolovskiy; M. M. Khobeish; M. V. Shapina; O. B. Shchukina (Современная ревматология)
Psoriasis (Ps), psoriatic arthritis (PsA), and inflammatory bowel diseases (IBDs) are characterized by a progressive course and frequently lead to disability; therefore, their early diagnosis with the assessment of a clinical phenotype and unfavorable prognostic factors and the timely initiation of therapy are important tasks. The paper provides the experts agreed opinion on the definition of the early stage of Ps, PsA, and IBDs, the goals of therapy and main unfavorable prognostic factors for the course of these diseases and gives the rationale for the early use of biological agents in patients with immune-mediated inflammatory diseases.